Karakteristik Pemahaman Mahasiswa dalam Mengonstruksi Bukti Matematis - Syamsuri, Syamsuri; Santosa, Cecep Anwar Hadi Firdos (UIN Sunan Ampel Surabaya, 2017)
The teaching and learning process in the mathematics undergraduate program emphasizes on the use of an axiomatic system and formal deduction. In this process, the students learn continuously about mathematical evidence, which can be referred to as the ability to build arguments based on their mathematical understanding. This article aims at describing the characteristics of students comprehension in constructing a mathematical evidence. A qualitative approach is applied in this study, which involves third-year students of Mathematics Education Department at the state university in Banten. Interviews are conducted to find out and clarify how the students construct and build mathematical evidence. The result shows that the students mathematical proof of comprehension can be classified into three types: holistic-global, partial-global, and partial-local. It is expected that the result of the study can be used as a source of consideration in determining appropriate learning strategies that can overcome students difficulties in constructing a mathematical evidence.